Interfaces: um estudo dos Núcleos de Estudo e Pesquisa do Programa de Estudos Pós-Graduados em Serviço Social da PUC SP - Leão, Paula Silva (2010)
This dissertation aimed to know the Centers for Education and Research Program of Postgraduate Studies in Social Work at PUC - SP and its contributions to training. The Centers for Study and Research at PUC-SP foster research in social work and are integrated by teachers and students of post-graduate and undergraduate. The prospect of these cores has been to foster research, aimed primarily at training human resources for research activity, both qualitative and quantitative. We performed the historical trajectory and deployment of Core Studies and Research in Social Work at PUC - SP and his contributions to the educational process of students. We mapped the Centers for Study and Research in Social Service Graduate PUC SP. Our aim was to know the history of guiding cores to understand their importance in the formation of knowledge for social work. We create a source of information on Nucleus. We conducted a study on the production of nuclei and their effects on training of students. We started this work with literature, we sought the production of Research in Social Work to visualize the proximity of the nuclei not only in research but seeking to understand how this contributes to the professional training. We had a basic reading of annals, journals, theses, dissertations, materials available online and documents in the library at PUC SP and Programme of Postgraduate Teaching in Social Work, PUC SP. The research methodology applied in this thesis was substantiated: the mapping of the Centers for Research in Social Service Graduate PUC SP, thus, understand how they work, their dynamic trajectories, outputs and impacts. We analyze their proposals and investigative training, the survey of formal and informal data on Nuclei registered in documentary and bibliographic study of cores from the Accreditation Program Post - Graduate Studies in Social Work, in interviews with the coordinators of the Education Centers and Research in Social Work at PUC - SP and the Focus Group with members of the Nuclei. So we did discourse analysis, simultaneously analyzing the Research in Social Work. The final remarks pointing to the fact that the nuclei are differentiated spaces for training, but they need greater visibility into promotion